Evaluation and Selection of Bacillus Species Based on Enzyme Production, Antimicrobial Activity, and Biofilm Synthesis as Direct-Fed Microbial Candidates for Poultry - Latorre, Juan D.; Hernandez-Velasco, Xochitl; Wolfenden, Ross E.; Vicente, Jose L.; Wolfenden, Amanda D.; Menconi, Anita; Bielke, Lisa R.; Hargis, Billy M.; Tellez, Guillermo (Frontiers in Veterinary Science, 2016)
Social concern about misuse of antibiotics as growth promoters (AGP) and generation of multidrug-resistant bacteria have restricted the dietary inclusion of antibiotics in livestock feed in several countries. Direct-fed microbials (DFM) are one of the multiple alternatives commonly evaluated as substitutes of AGP. Sporeformer bacteria from the genus Bacillus have been extensively investigated because of their extraordinary properties to form highly-resistant endospores, production of antimicrobial compounds and synthesize different exogenous enzymes. The purpose of the present study was to evaluate and select Bacillus spp. from environmental and poultry sources as DFM candidates, considering their enzyme production profile, biofilm synthesis capacity and pathogen-inhibition activity. Thirty one Bacillus isolates were screened for in vitro relative enzyme activity of amylase, protease, lipase and phytase using a selective media for each enzyme, with 3/31 strains selected as superior enzyme producers. These three isolates were identified as B. subtilis (1/3), and B. amyloliquefaciens (2/3) based on biochemical tests and 16S rRNA sequence analysis. For evaluation of biofilm synthesis, the generation of an adherent crystal violet-stained ring was determined in polypropylene tubes, resulting in 11/31 strains showing a strong biofilm formation. Moreover, all Bacillus strains were evaluated for growth inhibition activity against Salmonella enterica serovar Enteritidis (26/31), Escherichia coli (28/31) and Clostridioides difficile (29/31). Additionally, in previous in vitro and in vivo studies, these selected Bacillus strains have shown to be resistant to different biochemical conditions of the gastrointestinal tract of poultry. Results of the present study suggest that the selection and consumption of Bacillus-DFM, producing a variable set of enzymes and antimicrobial compounds may contribute to enhanced performance through improving nutrient digestibility, reducing intestinal viscosity, maintaining a beneficial gut microbiota and promoting healthy intestinal integrity in poultry.